SWOT Analysis and Development Alternatives Strategy of the Morowali Industrial Estate (IMIP) in Supporting Nickel Downstreaming and Regional Economic Growth - Zakaria Trismoyo; Sunardi, Sunardi; Eko Harsono; Bernard Hasibuan (Sean Institute, 2026)
Mineral downstreaming is a key industrial strategy in Indonesia to increase the added value of natural resources through metal-based manufacturing. The Morowali Industrial Park (IMIP) is one of the largest nickel downstreaming centers in Southeast Asia, contributing significantly to economic and social transformation in Morowali Regency. This research aims to evaluate internal and external strategic factors affecting IMIP using SWOT analysis. A qualitative descriptive method was applied based on a documentary video transcript supported by relevant literature review. The findings show IMIP’s strong internal advantages such as modern infrastructure, massive investment, a 60% increase in regional GDP, and more than 13,000 jobs created. Opportunities arise from the global demand for electric vehicle batteries and planned workforce expansion to 85,000 workers. However, weaknesses include dependence on a single commodity and limited local workforce capability. External threats include global nickel price volatility and competition among industrial zones. Based on the SWOT matrix, IMIP falls within the Growth Strategy quadrant, indicating strong potential for sustainable industrial expansion.